(untitled) - Berges, Steve (Hoboken, N.J., 2007)
Now in a newly updated and revised second edition, The Complete Guide to Flipping Properties covers all the ins and outs of buying, renovating, and reselling distressed properties at big profits. Steve Berges shows you how to excel at every aspect of flipping, from finding great deals, to analyzing property values, to negotiating sales, to closing deals. With new information on flipping in a soft market, this is the only guide you need to start turning a profit now.
Keywords: Real estate business